Histone modifications and p53 binding poise the p21 promoter for activation in human embryonic stem cells - Itahana, Yoko (Nature Publishing Group, 2016)
The high proliferation rate of embryonic stem cells (ESCs) is thought to arise partly from very low expression of p21. However, how p21 is suppressed in ESCs has been unclear. We found that p53 binds to the p21 promoter in human ESCs (hESCs) as efficiently as in differentiated human mesenchymal stem cells, however it does not promote p21 transcription in hESCs. We observed an enrichment for both the repressive histone H3K27me3 and activating histone H3K4me3 chromatin marks at the p21 locus in hESCs, suggesting it is a suppressed, bivalent domain which overrides activation by p53. Reducing H3K27me3 methylation in hESCs rescued p21 expression, and ectopic expression of p21 in hESCs triggered their differentiation. Further, we uncovered a subset of bivalent promoters bound by p53 in hESCs that are similarly induced upon differentiation in a p53-dependent manner, whereas p53 promotes the transcription of other target genes which do not show an enrichment of H3K27me3 in ESCs. Our studies reveal a unique epigenetic strategy used by ESCs to poise undesired p53 target genes, thus balancing the maintenance of pluripotency in the undifferentiated state with a robust response to differentiation signals, while utilizing p53 activity to maintain genomic stability and homeostasis in ESCs.